Education on natural rubber-based base isolator technology for SMKN 26 Jakarta students as an earthquake mitigation effort - Diyanti, Marsetya Aulia Rahma; Herlina, Liana; Kurniyaningrum, Endah; Wijaya, Usman; Kawanda, Aksan; Putri, Larasati Rizky (Community Empowerment, 2025)
Indonesia's high vulnerability to earthquakes, which often results in severe damage and casualties, necessitates disaster risk mitigation efforts based on science and technology. This community service activity aimed to improve disaster technology literacy and students' understanding of the working principles of earthquake-resistant structures. The focus was on introducing base isolator (earthquake damper) technology made from natural rubber for residential buildings. This activity was conducted at SMKN 26 Jakarta using interactive presentations, technology demonstrations, and participative discussion methods. An evaluation of understanding was administered to 66 participants using a pre-test and post-test design. The evaluation results showed that 100% of participants experienced an increase in understanding and knowledge after the activity. This indicates that the technology demonstration-based educational approach is effective in supporting disaster technology literacy at the vocational high school level.